Gunnar >>Nu<< - i idrætspolitisk lys - Bonde, Hans; Madsen, Jacob Westergaard (Forum for Idræt, 2008)
Artiklen omhandler Gunnar Valdemar Hansen, den mest centrale journalist af det dansk-tyske idrætssamarbejde under besættelsen. Hans Bonde & Jacob Westergaard Madsen: Gunnar »Nu« Denmark’s most famous sports journalist during the years, Gunnar Hansen, has always been celebrated as the great ikon of Danish national identity. He had a unique ability to create atmosphere and feelings of presence when he reported in the Danish radio broadcast on sporting events. However, this study demonstrates that Gunnar Hansen during the first years of German occupation believed that the Germans most likely was going to win the war and therefore actively engaged himself in Danish- German sporting relations becoming the main journalistic collaborator with the Germans. In October 1940 he conducted an interview with the German sports »Führer« Hans von Tschammer und Osten who promoted his vision of a renewed German body culture under the inspiration of Adolf Hitler. Also in the written press and in the weekly news in the cinemas Gunnar Hansen was engaged in reporting from the highly propagandistic German-Danish sporting arena. After the war, however, Gunnar Hansen presented himself as resistance fighter and produced an image of the sporting arena during the war as characterized by a »cold shoulder« towards the Germans.